1973
DOI: 10.1172/jci107156
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Secondary Hyperparathyroidism in Idiopathic Hypercalciuria

Abstract: A B S T R A C T Circulating levels of immunoreactive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
4
6

Year Published

1973
1973
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(119 citation statements)
references
References 15 publications
(21 reference statements)
7
102
4
6
Order By: Relevance
“…In one study, no change was found in PTH in IH patients during TZ treatment compared with baseline (37). However, in accordance with two other studies, we found a small, but significant, decrease in PTH related to TZ treatment (8,9). In our study, PTH was measured at multiple time points throughout the day, which may facilitate the detection of small, but potentially significant, changes in PTH related to TZ treatment.…”
Section: F595 Thiazide Increases Proximal Tubule Calcium Reabsorptionsupporting
confidence: 90%
“…In one study, no change was found in PTH in IH patients during TZ treatment compared with baseline (37). However, in accordance with two other studies, we found a small, but significant, decrease in PTH related to TZ treatment (8,9). In our study, PTH was measured at multiple time points throughout the day, which may facilitate the detection of small, but potentially significant, changes in PTH related to TZ treatment.…”
Section: F595 Thiazide Increases Proximal Tubule Calcium Reabsorptionsupporting
confidence: 90%
“…Although the results are not conclusive, these patients probably suffered from secondary hyperparathyroidism, as in the cases of renal hypercalciuria reported by Coe, Canterbury, Firpo, and Reiss (6). However, the features presented by these patients were the same as those found in patients with "normocalcemic" primary hyperparathyroidism (30).…”
Section: Discussionmentioning
confidence: 54%
“…There are two major proposed causes for the hypercalciuria in idiopathic hypercalciuria. The first is an enhanced intestinal absorption of calcium (absorptive hypercalciuria) (3)(4)(5) and the second is a primary defect in the renal tubular reabsorption of calcium ("renal leak" or renal hypercalciuria) (5,6). However, these pathogenetic mechanisms have not been fully documented or characterized and.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggested that excessive urinary calcium losses in CKD patients, who are prone to tenuous calcium balance because of relative calcitriol deficiency, may promote intermittent reductions in serum calcium with resulting spikes in PTH, which eventually manifest clinically as secondary hyperparathyroidism. This hypothesis is supported by studies in the general population and CKD that showed that excessive calciuria driven by loop diuretics was associated with elevated PTH (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 69%